Logika Hukum dalam Bidang Kedokteran - Widyarini I. W.; Irma Zaimatuddunia (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Logic is an important aspect of law and must take precedence in legal reasoning. Legal reasoning should be used to analyze and understand legal issues. Medical law is the branch of law that governs the relationship between doctors and patients. The methodology used in this study is socio-legal research that analyzes legal norms and facts that exist in society. The function of law is to protect, maintain order and tranquility, and provide justice and legal certainty. Legal protection of health services is important in maintaining public order and order.